Putusan Mediasi Sengketa Tata Usaha Negara, Pemilu di Kota Bekasi Pada Pemilu 2019 Dalam Perspektif Teori Keadilan John Rawls - Novita Ulya Hastuti (AL WASATH Jurnal Ilmu Hukum, 2023)
This study aims to determine the fulfillment of the principle of justice in the implementation of mediation by the Bawaslu of Bekasi City over election state administrative disputes (Sengketa Tata Usaha Negara) in the 2019 elections, which involved the PAN Party and the PPP Party with the Election Commission of Bekasi City. The principle of justice is one of the six principles of elections and one of the eleven principles of election administration as stipulated in Articles 2 and 3 of Law Number 7 of 2017. However, the operationalization of the fairness principles in the mediation procedure as part of the election dispute resolution system has not yet been translated into operational techniques in Bawaslu regulations. The researchers believe that the four parameters of justice, as stated by John Rawls, namely equal liberty, equal opportunity, and equal distribution, can be used as a reference for operationalizing the principles and principles of fairness. By examining the Dispute Resolution Report and mediation Decision documents issued by the Bekasi City Election Supervisory Body for the case using a legal philosophy approach, the researcher found that the implementation of mediation for the settlement of election state administrative disputes between the PAN Party and the PPP Party with the Bekasi City Election Commission was carried out by the Bekasi City Election Supervisory Body fulfilled the four parameters of justice as stated by John Rawls, namely equal liberty, equal opportunity, equal opportunity, and equal distribution. Based on the results of this study, the researcher recommends that Bawaslu improve the Bawaslu Regulations regarding election process dispute resolution by including these three parameters of justice in the mediation process.